Microstructure and oxidation resistance of composition gradients Nb-Si based alloy thin film - Wei Jiang; Meifeng Li; Jiangbo Sha; Chungen Zhou (Materials & Design, 2020)
High-throughput methods were developed to prepare multicomponent NbSi based (NbxCryTizSi1-x-y-zAl0.5) alloy film combinatorial libraries (x = 0 → 0.95, y = 0 → [0.95-x], z = 0 → [0.95-x-y]) with composition gradients. Oxidation behavior of the as-deposited film was investigated in dry air at 1250 °C. The results show that the as-deposited film is consisted of a mixture of amorphous and crystalline phases. Crystallized film is composed Cr2Nb, Nb5Si3 and Nbss phases after annealing. The film after oxidation at 1250 °C for different times exhibits three regions of distinct oxidation behavior. The composition for establishment of a protective CrNbO4 scale across the entire film is determined rapidly.